The application and effectiveness of yoga in prevention and rehabilitation of sport injuries in athletes participating in competitive sport - Ravi, S. (LASE Journal of Sport Science, 2016)
The purpose of the study is to review literature for scientific studies about application and effectiveness of yoga in rehabilitation & prevention of sports injuries in athletes participating in competitive sports. The author conducted a comprehensive search of open access articles of major scientific databases including PuBMed, SCIENCEDIRECT, EBSCO, SCOPUS, Web of Science, etc.. No significant scientific studies were found relating to the application of yoga in rehabilitation and prevention of sport injury. Four studies were selected based on inclusion criteria. One pilot study has included yoga as part of sport conditioning and has investigated use of yoga for flexibility and incidence of non-contact injuries in baseball athletes. The other studies include a clinical example that has used yoga as part of the seven point program in injury treatment of elite football players, an intervention that has included yoga in high-volume training program and a randomised control trial that has evaluated effect of yoga in flexibility and balance among athletes. Conclusions: There is scope for further studies to examine the effect of yoga as an adjunct intervention in rehabilitation of select sports injuries for athletes in competitive sport. There is potential to include sport-specific yoga programs in athletic training for prevention of non-contact injuries.